Wage Determination in Northeast Brazil - Verner, Dorte (World Bank, Washington, DC, 2012)
The author analyzes the labor markets in the Northeast region of Brazil that includes Pernambuco, Bahia, and Ceará states. Her findings show a rather heterogeneous impact pattern of individual characteristics on monthly wages across the wage distribution. That is, the magnitude of the effect of a wage determinant is different depending on whether the worker is placed in the lower, median, or top of the wage distribution. The findings reveal that basic schooling matters for all four geographical areas and across the income distribution. However, poor workers are awarded lower returns than their richer peers, and in Bahia and Ceará, the poor do not obtain any returns to basic schooling. Furthermore, the impact of 5-8 or 9-11 years of education is larger than that of 1-4 years of completed education. The returns obtained by a median worker are higher in Ceará and Pernambuco than in Bahia. Finally, completed tertiary education offers the largest returns of all levels of education. The median worker receives a premium of 105, 249, and 216 percent in Ceará, Pernambuco, and Bahia, respectively. Hence, one direct policy implication is to increase the quality of education, in particular in poorer neighborhoods. Experience impacts positively on wages and it increases with age until workers reach 50 years of age. However, returns to experience are falling significantly across the wage distribution. For the poor and younger generations, experience contributes more to wages than education. The occupation of workers is important for wage determination. All workers in the included occupational groups are paid more than workers engaged in agricultural activities. Workers employed as technicians or administrators obtain the highest returns. The white/nonwhite wage disparity reveals that white workers are paid 17 percent more than their nonwhite co-workers, taking into account other characteristics. Gender disparities are large in the Northeast and heterogeneous across the wage distribution. The time spent in the current state impacts adversely on wages. That is, those that have stayed earn, on average, less than the newcomers. There are no considerable differences between male and female workers. Union membership has a positive impact on workers' wages.